Gestational Diabetes Independently Increases Birth Length and Augments the Effects of Maternal BMI on Birth Weight: A Retrospective Cohort Study - Byström, Magdalena; Liu, Anthony; Quinton, Ann Elizabeth; Champion, Bernard Linton; Mann, Kristy; Peek, Michael; Nanan, Ralph Kay Heinrich (Frontiers in Pediatrics, 2014)
Objective: To investigate the effect of the interaction between gestational diabetes mellitus (GDM) and maternal body mass index (BMI) on the individual neonatal growth parameters. Design: Retrospective cohort study. Setting: A tertiary maternity service in Sydney, Australia, between 2005 and 2009. Population: A cohort of 8859 women. Methods: Generalized linear models. Main outcome measures: Neonatal growth parameters, represented by z-scores for infant birth weight (BW), birth length (BL), and head circumference (HC) in GDM and non-GDM groups. Results: Only GDM alone had an independent and positive effect on BL (p = 0.02) but not on BW or HC. In addition, in pregnancies complicated with GDM, the association between maternal weight and BW was significantly stronger (p < 0.001). In combination, GDM and maternal BMI significantly affected z-score differences between BW and BL (p < 0.001), in that underweight mothers had babies that were lighter relative to their length and inversely obese mothers had babies that were heavier relative to their length. Conclusion: GDM independently influences BL and increases the association between maternal BMI and BW. In accordance with the hypothesis of the fetal origins of health and disease, the pronounced effects of GDM on fetal growth patterns demonstrated in this study are likely to influence long-term health outcomes in children.